2004
DOI: 10.1074/jbc.m313672200
|View full text |Cite
|
Sign up to set email alerts
|

MAGP-2 Has Multiple Binding Regions on Fibrillins and Has Covalent Periodic Association with Fibrillin-containing Microfibrils

Abstract: The interactions of microfibril-associated glycoprotein (MAGP)-2 have been investigated with fibrillins and fibrillin-containing microfibrils. Solid phase binding assays were conducted with recombinant fragments covering fibrillin-1 and most of fibrillin-2. MAGP-2, and its structure relative MAGP-1, were found to bind two fragments spanning the N-terminal half of fibrillin-1 and an N-terminal fragment of fibrillin-2. Blocking experiments indicated that MAGP-2 had a binding site(s) close to the N terminus of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
(39 reference statements)
0
39
0
Order By: Relevance
“…Additional antibody labeling studies using epitopemapped mAbs have been used to support various arrangements of fibrillin-1 within the microfibril (11, 12, 16). Antibodies spe- cific for microfibril-associated glycoprotein-1 and -2 (MAGP-1 and -2) have also been used to demonstrate the presence of microfibril-associated glycoproteins near or on the globular beads in the microfibril (21). Double labeling with antibodies specific for fibrillin-1 and -2 showed that fetal microfibrils are composed of both fibrillins (15).…”
Section: Discussionmentioning
confidence: 99%
“…Additional antibody labeling studies using epitopemapped mAbs have been used to support various arrangements of fibrillin-1 within the microfibril (11, 12, 16). Antibodies spe- cific for microfibril-associated glycoprotein-1 and -2 (MAGP-1 and -2) have also been used to demonstrate the presence of microfibril-associated glycoproteins near or on the globular beads in the microfibril (21). Double labeling with antibodies specific for fibrillin-1 and -2 showed that fetal microfibrils are composed of both fibrillins (15).…”
Section: Discussionmentioning
confidence: 99%
“…MAGP-1 has also been shown to bind to fibrillin-2 in yeast two-hybrid, ligand blotting, and solid phase binding assays (Werneck et al, 2004). MAGP-2 binds to fibrillin-1 and -2 in yeast twohybrid studies (Penner et al, 2002) and in solid phase binding assays (Hanssen et al, 2004). The ability of MAGP-1 to bind both tropoelastin and fibrillin suggested that it might play an important role in elastic fiber assembly by serving as a bridging molecule between its two binding partners.…”
Section: Magp-1 and Magp-2mentioning
confidence: 99%
“…After washing three times with TBS, the membranes were incubated for 2 h with monoclonal antibody 16E12 (1:50) in binding buffer against the soluble ligand. 27 The membranes were incubated for 2 h with horseradish peroxidase-conjugated goat-anti mouse antibodies (1:800 diluted in binding buffer) followed by detection with ECL (Amersham, USA) according to the protocol of the manufacturer. Densitometric scanning was performed using ImageJ (Version 1.41) after background subtraction.…”
Section: Slot Blot-overlay Assaymentioning
confidence: 99%